`Let them get on with it`: Coaches` perceptions of their roles and coaching practices during Olympic and Paralympic Games - Ritchie, D.; Allen, J. (International Sport Coaching Journal, 2015)
How coaches prepare and perform is critical for athletes` performances (Gould, Guinan, Greenleaf & Chung, 2002), however, little is known about coaches` roles and coaching practices during major competitions such as the Olympic or Paralympic Games. To assist coaches in their efforts to improve athletes` performances in competition environments, greater understanding is needed about the coaching process during major competitions and how coaches prepare and perform. Therefore, the purpose of the current study was to examine track and field coaches` perceptions of their roles and coaching practices during competition at major events. Eight coaches, seven male and one female, who had coached one or more athletes to an Olympic or Paralympic medal were interviewed. Inductive content analysis indicated that creating an athlete focused supportive environment, detailed preparation and planning, use of effective observation and limited intervention, coach and athlete psychological preparation and managing the process were salient during competition at major events. These findings suggest that during major competition the coach`s role is supportive and facilitative. Actions are largely unobtrusive and in response to athletes` needs, but remain as detailed as other phases of the coaching process. The findings are discussed in relation to the coach as orchestrator.